2008
DOI: 10.2174/138161208784480144
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 in Synaptic Signaling

Abstract: Cyclooxygenase-2 (COX-2), a rate-limiting enzyme converting arachidonic acid to prostaglandins and a key player in neuroinflammation, has been implicated in the pathogenesis of neurodegenerative diseases such as multiple sclerosis, Parkinson's and Alzheimer's diseases, and in traumatic brain injury-and ischemia-induced neuronal damage, and epileptogenesis. Accumulated information suggests that the contribution of COX-2 to neuropathology is associated with its involvement in synaptic modification. Inhibition or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
116
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(123 citation statements)
references
References 139 publications
1
116
0
1
Order By: Relevance
“…The major n-6 fatty acid in Western diets is LA, with this fatty acid representing about 90% of all the polyunsaturated fatty acids in North American diets. In the brain, however, ARA plays critical roles as a precursor of eicosanoids important in synaptic signaling, as a fatty acyl moiety in the anadamides 2-arachidonyl glycerol and arachidonyl ethanolamide, as well as other signaling molecules [13][14][15][49][50][51] . Although the possibility that increased LA or altered ARA metabolism may contribute to PPD has received little attention, altered ARA metabolism and anadamides are believed to be important in several neuropsychiatric diseases, including depression [49,50] .…”
Section: Discussionmentioning
confidence: 99%
“…The major n-6 fatty acid in Western diets is LA, with this fatty acid representing about 90% of all the polyunsaturated fatty acids in North American diets. In the brain, however, ARA plays critical roles as a precursor of eicosanoids important in synaptic signaling, as a fatty acyl moiety in the anadamides 2-arachidonyl glycerol and arachidonyl ethanolamide, as well as other signaling molecules [13][14][15][49][50][51] . Although the possibility that increased LA or altered ARA metabolism may contribute to PPD has received little attention, altered ARA metabolism and anadamides are believed to be important in several neuropsychiatric diseases, including depression [49,50] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, COX-2 is responsible for the production of large amounts of proinflammatory PGs at inflammatory sites. Therefore, as chronic phases of inflammation and infection correlate strongly with the increased production of PGE 2 , substances that inhibit PGE 2 production could be of therapeutic benefit [8][9][10]. Recently, it was reported that COS could inhibit nitric oxide (NO) formation in macrophage RAW 264.7 cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…Yang and Chen suggested that COX-2 along with PGE2 regulate cell membrane excitability and long term synaptic plasticity in the hippocampus. 12 Oliveira et al reported that prostaglandin mediates induced inflammation in brain, which has epileptogenic properties. 13 Choi et al reported that glutamatergic neurons present in the hippocampus and cerebral cortex play a prominent role in onset of seizures, and also that COX-2 is mainly expressed within these regions.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 PGE2 generated by induced brain COX-2 facilitates the recurrence of hippocampal seizure by stimulating neuronal excitability immediately after a seizure episode. 17 Chen et al also reported the regulatory role of PGE2 in membrane excitability and synaptic transmission in hippocampal neurons and suggested that the induced COX-2 accelerated the hyperexcitotoxicity immediately after seizure.…”
Section: Discussionmentioning
confidence: 99%